Seroprevalence of leptospirosis among people in Shabramant Village, Egypt - Amgad A Elzahaby; Samy Zaky; Nawal A Hafez Hassanain; El-Sayed R Hassan; Mohey A Hafez Hassanain; Mohamed Hegazy; Ahmed M Maher (Wolters Kluwer Medknow Publications, 2018)
Background Leptospirosis is considered as the most common zoonosis in the world. Leptospirosis has a multiorgan affection that can affect nearly any organ in a classical, rare or unusual presentation and complications. This may include hepatic, renal, pulmonary, meninges and cardiac affections. Aim The purposes of this study were estimating leptospiral infection prevalence among people living in Shabramant village at El-Giza Governorate and identifying associated environmental and behavioral risk factors for the infection. Patients and methods This study was designed to be a cross-sectional study conducted during the period from June 2013 to May 2014. Our study included 100 participants based on history taking and laboratory investigations; a structured questionnaire was administered to collect information on individuals' potential risk factors for leptospiral infection. Microagglutination test was performed using five Leptospira serovars: Leptospira int. icterohaemorrhagiae, Leptospira int. canicola, Leptospira int. pomona, Leptospira int. grippotyphosa and Leptospira int. wolffi to determine the presence of leptospiral antibodies and their titers in the sera of investigated patients. Results Our study found leptospirosis disease to be common among studied cases (44%), and L. icterohemorrhagiae was the only serovar detected among the studied cases. Middle-aged female patients were predominantly affected (52.6%); hence, age and sex can be regarded as risk factors of leptospirosis. Coinfections by other pathogens were also noted in this study; 22.2% of the 44 cases included had positivity for hepatitis C virus antibodies, which can be regarded as a risk factor for acquiring this disease. Also, living close to places inhabited by rodents and animals was considered as an important risk factor for exposure to such infections, and measures should be developed to minimize exposure to these animals. Conclusion It can be concluded that leptospirosis is an important neglected zoonotic disease despite its high prevalence. We recommend adding Leptospira infection to the list of possible diseases among febrile patients and increasing the awareness of the fever hospital clinicians about leptospirosis.